Perjuangan Perempuan pada Novel Teruslah Bodoh Jangan Pintar Karya Tere Liye (Kajian Ekofeminisme) - Yusnia Damanik; Elly Prihasti Wuriyani; Januarsyah Daulay (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to know and find the form of oppression experienced by female characters and nature as well as how women's struggle for nature and environmental preservation in the novel Teruslah Bodoh Jangan Pintar by Tere Liye. The method used in this research is descriptive qualitative. The results of this study are the forms of oppression against nature and women in the novel Teruslah Bodoh Jangan Pintar by Tere Liye can be seen from the many forms of oppression in the novel, based on De'Eaubonne's ecofeminism theory divided into two, namely the first exploitation of nature and women such as indiscriminate land conversion, illegal logging. The second is environmental and human degradation such as poor soil quality due to mining waste and degrading human dignity. The form of women's struggle against nature and women in the novel Teruslah Bodoh Jangan Pintar by Tere Liye can be in three aspects, namely the first liberation from the patriarchal system. Second, the protection of the environment and natural resources. Third, criticism of exploitation and capitalism.